C―H···O hydrogen bonding interactions for sterically hindered phenols and their phenoxyl radicals. (27th December 2018) - Wang, Jinhu; Liu, Chunli; Liu, Xuejing; Shao, Linjun; Zhang, Xian‐Man
Abstract: Sterically hindered phenols have been widely used as chain‐breaking antioxidants in chemical and polymeric industries, and the remarkable stabilities of their phenoxyl radicals are generally attributed to the steric effects and resonance stabilization of the unpaired electron into the aromatic ring. Non‐covalent interaction (NCI) analysis shows that there are four intramolecular C―H···O hydrogen bonds between oxygen atom and the ortho t ‐butyl C―H bonds for the sterically hindered phenoxyl radicals and their phenolic precursors. The C―H···O hydrogen bonds can be directly visualized and quantified from the reduced density gradient NCI isosurfaces and atoms‐in‐molecules analysis, respectively. Furthermore, the phenolic O―H bond strength decreases gradually with increasing volume of the ortho alkyl substituents in three different phenol model systems (Table 5). The nice linear correlation of the O―H bond dissociation enthalpies with the Taft's steric parameters (Figure 8) provides additional evidences to support formation of the intramolecular C―H···O hydrogen bonds between oxygen atom and the ortho t ‐alkyl C―H bonds. Abstract : Reduced density gradient vs sign(λ2 ) ρ plot (a) and RDG isosurfaces plot (b) for 2, 6‐di‐ t ‐butylphenol.